Experience gained in the research-to-development continuum: livestock research for sustainable livelihoods in the East African mountains - Mohamed-Saleem, M.A. (International Mountain Society (IMS) and United Nations University, 2001)
The east African mountain region provides living testimony to what can go wrong when the traditional balance between people, their habitat and the socio-economic context breaks down. The problems posed by population growth, land pressure, food scarcity, and degradation of a fragile environment with finite natural resources are aggravated by insecurity, civil war and cross-border refugee camps. In the face of these odds, the CGIAR International Livestock Research Institute (ILRI) and its predecessor, ILCA, have been working to improve people's livelihoods in Ethiopia since 1974. ILRI believes that the needs of mountain regions can be met sustainably by tapping the potentials of different ecological niches more efficiently, particularly in the area of livestock production. The present paper presents examples of ILRI's development-oriented research and evokes the challenges encountered by research that targets broad development goals.